The genus Alurnus Fabricius, 1775 (Chrysomelidae: Cassidinae: Alurnini) in Colombia with four new species records and an updated checklist in the country - Rendón-Ramírez, Alejandra; Vergara-Navarro, Erika Valentina; Quiroz-Gamboa, John Alveiro (Zootaxa, 2024)
In Colombia, the taxonomy of leaf beetles (Chrysomelidae) shows information gaps in the composition, biology, richness, distribution, among others, although most of them are of agricultural importance. The genus Alurnus is distributed in the Neotropical Region and it is the most specious genus of the tribe Alurnini (Chrysomelidae, Cassidinae). Species of this genus have been reported in association with palms of the family Arecaceae. Previous studies of Alurnus recorded 12 species for Colombia. In this study, 64 specimens were analyzed from 14 Colombian entomological collections, confirming previous records of seven species and reporting four new records for Colombia. This study provides the names of associations and host plants for some species, and the geographic distribution for each one.